Urothelial carcinoma of the ureter, giant rectal stone and sigmoid carcinoma 55 years after ureterosigmoidostomy - Wilhelm, Torsten; Knoll, Thomas; Weisser, Gerald; Grobholz, Rainer; Köhrmann, Kai-Uwe; Post, Stefan (Scandinavian journal of urology and nephrology, 2006)
We present the case of a unique accumulation of complications 55 years after ureterosigmoidostomy for bladder exstrophy and discuss possible implications for follow-up strategies.